Anatomical Respons of Ajwa Dates Sprouts (Phoenix dactylifera L.) to Water Availabiity and Light Intensity - Armanda, Dian Triastari (JOURNAL OF NATURAL SCIENCES AND MATHEMATICS RESEARCH, 2015)
The biggest moslem population in the world Indonesia still has high dependency on importing date palms from another country. Ajwa dates (Phoenix dactylifera L.) is one of special date palm cultivar whichÂ  had cultivated since 5000 BC in arid climate area in Saudi Arabia/Al-Madinah Al-Monwarah. Adaptation and optimation of environmental factors for Ajwa dates cultivation in Indonesia important to be conducted to meet the date palm demand of this country.This papers is a study on anatomical responses of Ajwa dates sprouts to water availibility and light intensity has been conducted. Ajwa date sprouts has been exposed to three shade variations (without shade, 50% shade, and 90% shade) and four water availibility variations (25%, 50%, 75%, dan 100% of the field capacity). Data taken from day 0 until 45th day of germination. Morphological parameters which observed and analyzed were the length of the leaf blade and the sprouts root length. Anatomical parameters which observedÂ  and analyzed were the radius of the root, the stele diameter, number of leaves, leaf thickness, and stomatal diameter. Variations on water availibility and light intensity gives the same effect (not significantly different), consequently the most optimal variation treatment was unknown. Advanced research need to be conducted to gain more complete information regarding the optimization of environmental factors for the cultivation of Ajwa date.